2007
DOI: 10.1529/biophysj.107.112615
|View full text |Cite
|
Sign up to set email alerts
|

Rigidification of Neutral Lipid Bilayers in the Presence of Salts

Abstract: We studied the influence of sodium and calcium chloride on the global and local membrane properties of fluid palmitoyl-oleoyl phosphatidylcholine bilayers, applying synchrotron small-angle x-ray diffraction, spin-labeling electron paramagnetic resonance spectroscopy, and differential scanning calorimetry, as well as simultaneous density and acoustic measurements. The salt concentration was varied over a wide range from 0 to 5 M. We found that NaCl leads to a continuous swelling of the bilayers, whereas the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
237
2
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(282 citation statements)
references
References 63 publications
(114 reference statements)
38
237
2
5
Order By: Relevance
“…As we 70 and others 65,67,76,77 have recently demonstrated, small cations such as Na + bind to the ester/carbonyl atoms of phospholipids, inducing a slight enhancement of the lipid order (whereas common counter ions such as Cl À remain firmly in the aqueous phase and do not affect the lipids). Although we have not included ions in these simulations, we expect that the addition of a salt such as NaCl would lead to a systematic ordering effect, identical for all sterols along the series, and therefore all comparative conclusions of this study would be unchanged.…”
Section: View Article Onlinementioning
confidence: 70%
“…As we 70 and others 65,67,76,77 have recently demonstrated, small cations such as Na + bind to the ester/carbonyl atoms of phospholipids, inducing a slight enhancement of the lipid order (whereas common counter ions such as Cl À remain firmly in the aqueous phase and do not affect the lipids). Although we have not included ions in these simulations, we expect that the addition of a salt such as NaCl would lead to a systematic ordering effect, identical for all sterols along the series, and therefore all comparative conclusions of this study would be unchanged.…”
Section: View Article Onlinementioning
confidence: 70%
“…28,30 During the past decade, however, this view has been challenged. Indirect evidence from infrared spectroscopy, 32 fluorescence correlation spectroscopy, 33 atomic force microscopy, 35,36 smallangle X-ray diffraction, 41 spin-labeling electron paramagnetic resonance spectroscopy, 41 and calorimetric 33,41 studies suggest the possibility of Na + interacting with lipid carbonyl oxygens, binding lipids into complexes, and thus leading to detectable changes in area per lipid, bilayer thickness and rigidity, 41 as Hopping greatly promoted the lateral diffusion of Na + within the carbonyl region. The lateral mean squared displacement (MSD) of sodiums continuously complexed with DMPC (thick dashed red line) is considerably smaller than if lipid-free hops are allowed (thick continuous black).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that anionic 4, [22][23][24][25] and cationic 26,27 membranes interact readily with their counterions (especially divalent ones), whereas the interactions of zwitterionic lipid bilayers with salt ions appear rather sensitive to the size and valency of ions. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] As for molecular-level computational studies, the increase in computing power in the past few years has made it possible to extend computer simulations beyond the relatively long relaxation times of tens to hundreds of nanoseconds required for equilibration of ions in lipid/water systems. Although most computational studies by far have focused on the effects of salt ions on zwitterionic (neutral) lipid bilayers, 33,[42][43][44][45][46][47][48][49][50][51][52][53] there is also an increasing number of studies on anionic [54][55][56][57][58][59] and cationic 60,61 lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the order of POPC acyl chains in the presence of NaCl have been described both experimentally 74 and by MD simulations. 60,62,75 These MD studies showed that the chloride ion has an external distribution, with a maximum clearly outside that of the POPC head group atoms, and probably has little if any impact on acyl View Article Online chain order.…”
Section: View Article Onlinementioning
confidence: 99%